2013
DOI: 10.4103/2045-080x.123224
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of adverse drug event-related admissions at a local hospital in Malaysia

Abstract: Aims:To determine the prevalence of adverse drug event (ADE)-related admissions and the related drugs. Setting and Designs: This study was conducted prospectively in two medical wards in Malaysia. Subjects and Methods: Information was collected from patients' medical and medication charts over a period of 24 weeks. All screened patients were assessed using a list of criteria and were classified into: Therapeutic failure (TF), adverse drug reaction (ADR), medication error (ME), and drug overdose (DO). Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 30 publications
6
32
0
Order By: Relevance
“…4 Medication errors may be committed by both inexperienced and experienced persons like doctors, pharmacists, dentists, patients, manufacturers and other healthcare providers. 5 The present study has been undertaken with the aim of finding out the incidences of medication errors in indoor patients of a tertiary care center. The purpose of the present study was to evaluate demography about medication errors, drugdrug interactions and rationality of Prescription in general medicine ward and surgery ward at a tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%
“…4 Medication errors may be committed by both inexperienced and experienced persons like doctors, pharmacists, dentists, patients, manufacturers and other healthcare providers. 5 The present study has been undertaken with the aim of finding out the incidences of medication errors in indoor patients of a tertiary care center. The purpose of the present study was to evaluate demography about medication errors, drugdrug interactions and rationality of Prescription in general medicine ward and surgery ward at a tertiary care hospital.…”
Section: Introductionmentioning
confidence: 99%
“…The Malaysian Adverse Drug Reaction Monitoring Program receives and monitors spontaneous reporting on ADRs [9]; however, besides annual reports on ADRs from this monitoring program, data on other types of ADEs are still lacking in Malaysia. In a recent study conducted in two medical wards of a government hospital, Karuppannan et al [10] estimated the prevalence of ADE-related hospital admissions to be 39%; however, data on patients seeking treatment for an ADE in the ED are often not reflected in hospital-based studies because not all of these patients may eventually get admitted [11]. In this study, we sought to determine factors associated with ED visits resulting from medication use.…”
Section: Introductionmentioning
confidence: 98%
“…In our study anti-diabetic drugs were used in 30.2% of study population where as it was 40% reported in another study 6 . Most commonly used antidiabetic drug was metformin either alone or in combination (75.6%), followed by sulfonylureas (56.0%).…”
Section: According To Nhms 2011mentioning
confidence: 99%
“…Higher drug intake may also subject them to the problems of polypharmacy like drug-drug and drug-disease interactions, decreased compliance in prescribed drugs, increased iatrogenic illnesses leading to increased healthcare related costs 6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation